The Implementation of Harrod-Domar Economic Growth Model in North Sulawesi, Indonesia - Jeane Rumawir (International Journal of Applied Business and International Management, 2019)
The study aimed to: Understand and analyze the poors perceptions and attitude on poverty reduction programs, identify, elaborate, and analyzethe term poor among the poor people and identify and analyze meaning and expectation on poverty reduction program. This research applies developmental research method; the analysis model uses SEM (Structural Equation Modeling). Before applying this model, goodness of fit was conducted in order to find out whether this model can be accepted or not. The model could achived goodness of fit; therefore, all variables could follow hypothesis test. The research result showed the changed in economic structures have direct significant influence on the government’s stimulus and economic growth. Capital establishment also has direct unsignificant effect on the government’s stimulus. Capitall establishment has significant influence to the economic growth and the socio cultural influence does not have significant influence to the economic growth. These results indicate that the greater stimulus of the government signified by precise goals leads to better economic growth.